2012
DOI: 10.1186/1744-8069-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Fibromyalgia Display Less Functional Connectivity in the Brain's Pain Inhibitory Network

Abstract: BackgroundThere is evidence for augmented processing of pain and impaired endogenous pain inhibition in Fibromyalgia syndrome (FM). In order to fully understand the mechanisms involved in FM pathology, there is a need for closer investigation of endogenous pain modulation. In the present study, we compared the functional connectivity of the descending pain inhibitory network in age-matched FM patients and healthy controls (HC).We performed functional magnetic resonance imaging (fMRI) in 42 subjects; 14 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(193 citation statements)
references
References 62 publications
5
185
0
3
Order By: Relevance
“…Studies that correlate CPM with brain processes have revealed modifications in the activation of different brain areas 14 and in the functional connectivity of the descending inhibitory system. 15 The origin of these changes, however, remains unclear.…”
Section: Cpm In Low Back Painmentioning
confidence: 99%
“…Studies that correlate CPM with brain processes have revealed modifications in the activation of different brain areas 14 and in the functional connectivity of the descending inhibitory system. 15 The origin of these changes, however, remains unclear.…”
Section: Cpm In Low Back Painmentioning
confidence: 99%
“…One study found that FMS patients exhibited higher sensitivity to pain provocation than controls and that they required less pressure to evoke equal pain, but they failed to respond to pain provocation in the primary link in the descending pain-regulating system (the rostral anterior cingulate cortex) (Flodin et al, 2014). Another study comparing the functional connectivity of the descending pain inhibitory network in age-matched FMS patients and healthy controls found that patients displayed less connectivity within the brain's pain inhibitory network during calibrated pressure pain compared with healthy controls (Jensen et al, 2012).…”
Section: Pathogenesismentioning
confidence: 99%
“…A number of studies have provided further evidence of dysfunctional connectivity of the pain network in FMS (Jensen et al, 2012;Flodin et al, 2014). One study found that FMS patients exhibited higher sensitivity to pain provocation than controls and that they required less pressure to evoke equal pain, but they failed to respond to pain provocation in the primary link in the descending pain-regulating system (the rostral anterior cingulate cortex) (Flodin et al, 2014).…”
Section: Pathogenesismentioning
confidence: 99%
“…Contrariamente, se constata una reducción del VSG en la circunvolución temporal superior (71,73), INS (71,77,78), COF lateral (72) y medial (71,74,76,79,80), CCA rostral (61,72,76,77,79), CCP (71,76,80), precuneus izquierdo (71,75,76), TAL (48,73), amígdala (48,61), circunvolución parahipocámpica (61,76,79), putamen (48) y SGP (48,75). Es de especial relevancia el decremento del VSG y grosor de la corteza en la CCA en su porción rostral, así como una reducción significativa del VSB en la CCA rostral izquierda y en la COF lateral izquierda (72), puesto que ello conlleva a una desregulación de los mecanismos inhibitorios endógenos en la FM (33,69,72,75,78).…”
Section: Cambios Morfológicos Y Estructuralesunclassified